Selective Radiologic Imaging in The Diagnosis of Knee Osteoarthritis : a Systematic Literature Review - Yuslila, Ewi; Nadhrati Surura, Hedya; Khairul Fikri, Handy; Mukhlis Wardani, Pitra; Fitria, Mawaddah; Al Bukhari, Al Bukhari (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2025)
This literature study helps clinicians in clinical practice in choosing the right radiological imaging in the diagnosis of Knee Osteoarthritis (KOA) according to the patient's condition. Reference sources were obtained systematically from reputable databases; PubMed, Science Direct, Springer Link, Cochrane Library, and Google Scholar with a range of publication years from 2017 to 2024. The keywords used in this literature searching process are "Knee Osteoarthritis" "Imaging", "Radiology", "Radiography", "MRI", "Ultrasound", "CT", "OCT", and "Nuclear Medicine Bone Scan". A systematic literature search using the PRISMA flow chart resulted in 3,866 articles which were then selected based on the inclusion and exclusion criteria of 26 articles. Articles were selected based on their relevance with a focus on radiologic imaging techniques in knee osteoarthritis cases. This literature study shows that Radiographic techniques are the first-line imaging modality in establishing the diagnosis of KOA in symptomatic patients. MRI is primarily used if a patient with suspected KOA is found to be asymptomatic and may be recommended for examination. USG is used because it is most commonly available and inexpensive, CT-Scan is used if atypical KOA cases are suspected. NMBS and OCT are used for suspected KOA with certain medical conditions. In clinical practice, the flexibility of imaging selection needs to be adjusted according to clinical symptoms, risk factors, suspected atypical cases, cost, and equipment availability.